A historical exploration of the internal political factors in the fall of apartheid : The case of Lebowa Bantustan,1970-1994 - Mokgawa, Amos Pheeha (University of Limpopo (Turfloop Campus), 2008)
Refer to document
Thesis (M.A. (History)) --University of Limpopo, 2008
Keywords: Internal political factors; Apartheid; 320.560968; Politics in literature; History -- Research -- South Africa; Apartheid -- South Africa